Within walking distance : creating livable communities for all - Langdon, Philip (Island Press, 2017)
For five thousand years, human settlements were nearly always compact places. Everything a person needed on a regular basis lay within walking distance. But then the great project of the twentieth century--sorting people, businesses, and activities into separate zones, scattered across vast metropolises--took hold, exacting its toll on human health, natural resources, and the climate. Living where things were beyond walking distance ultimately became, for many people, a recipe for frustration. As a result, many Americans have begun seeking compact, walkable communities or looking for ways to make their current neighborhood better connected, more self-sufficient, and more pleasurable. In this volume, the author looks at why and how Americans are shifting toward a more human-scale way of building and living. He shows how people are creating, improving, and caring for walkable communities. There is no one-size-fits-all approach. Starting conditions differ radically, as do the attitudes and interests of residents. To draw the most important lessons, Langdon spent time in six communities that differ in size, history, wealth, diversity, and education, yet share crucial traits: compactness, a mix of uses and activities, and human scale. The six are Center City Philadelphia; the East Rock section of New Haven, Connecticut; Brattleboro, Vermont; the Little Village section of Chicago; the Pearl District in Portland, Oregon; and the Cotton District in Starkville, Mississippi. In these communities, Langdon examines safe, comfortable streets; sociable sidewalks; how buildings connect to the public realm; bicycling; public transportation; and incorporation of nature and parks into city or town life. In all these varied settings, he pays special attention to a vital ingredient: local commitment. To improve conditions and opportunities for everyone, the author argues that places where the best of life is within walking distance ought to be at the core of our thinking. This book is for anyone who wants to understand what can be done to build, rebuild, or improve a community while retaining the things that make it distinctive.- Resumé vydavatel
Keywords: urbanismus -- Spojené státy americké; pěší zóny -- Spojené státy americké; místní rozvoj -- Spojené státy americké; veřejný prostor -- Spojené státy americké; city planning -- United States; pedestrian areas -- United States; community development -- United States; public space -- United States; elektronické knihy; monografie; electronic books; monographs